基于有限元法的蜗轮蜗杆热力学分析 - 陈海峰; 王欢; 翟培培 (Jixie chuandong)
Worm- gear and worm can produce great heat at work,which makes them deformation,and the thermal stress is produced. Taking the worm- gear and worm of a single- stage worm reducer as the research object,the solid model is built by SolidWorks and imported to ANSYS WORKBENCH. The thermal analysis and the thermodynamic analysis are carried out. Through the parametric design method,the influence of the temperature on the maximum equivalent stress under the given structural load is analyzed,the changing curve of the maximum equivalent stress with the temperature is obtained.